Camera Monitoring at volcanoes - Witt, Tanja Ivonne (2018)
Basaltic fissure eruptions, such as on Hawai'i or on Iceland, are thought to be driven by the lateral propagation of feeder dikes and graben subsidence. Associated solid earth processes, such as deformation and structural development, are well studied by means of geophysical and geodetic technologies. The eruptions themselves, lava fountaining and venting dynamics, in turn, have been much less investigated due to hazardous access, local dimension, fast processes, and resulting poor data availability. This thesis provides a detailed quantitative understanding of the shape and dynamics of lava fountains and the morphological changes at their respective eruption sites. For this purpose, I apply image processing techniques, including drones and fixed installed cameras, to the sequence of frames of video records from two well-known fissure eruptions in Hawai'i and Iceland. This way I extract the dimensions of multiple lava fountains, visible in all frames. By putting these results together and considering the acquisition times of the frames I quantify the variations in height, width and eruption velocity of the lava fountains. Then I analyse these time-series in both time and frequency domains and investigate the similarities and correlations between adjacent lava fountains. Following this procedure, I am able to link the dynamics of the individual lava fountains to physical parameters of the magma transport in the feeder dyke of the fountains. The first case study in this thesis focuses on the March 2011 Pu'u'O'o eruption, Hawai'i, where a continuous pulsating behaviour at all eight lava fountains has been observed. The lava fountains, even those from different parts of the fissure that are closely connected, show a similar frequency content and eruption behaviour. The regular pattern in the heights of lava fountain suggests a controlling process within the magma feeder system like a hydraulic connection in the underlying dyke, affecting or even controlling the pulsating behaviour. The second case study addresses ...